The symbolic thinking ability of kindergarten students in central Aceh through Montessori games based on gender - Elfi Rahmadhani; Septia Wahyuni; Lola Mandasari (International Journal of Evaluation and Research in Education (IJERE), 2023)
Student’s cognitive abilities can be developed early, including thinking logically and symbolically and problem-solving using various methods. Therefore, this quantitative descriptive research aims to determine the symbolic thinking ability of kindergarten students through Montessori games based on gender. The subjects of this study were 112 kindergarten students from eight schools in the Central Aceh district who were selected by random sampling. Data processing techniques include editing, coding, scoring, and tabulation. The analysis was carried out using a frequency table with guidelines for assessing child development. Data were obtained from tests, observations, and interviews. Based on the analysis, it is known that the symbolic thinking abilities of male and female students are at the level of developing as expected. There are still students at the beginning to develop and undeveloped levels for both male and female students in this ability. There are differences in ability between male and female students, especially in indicators: i) Mentioning numbers 1-10 and ii) Counting and matching numbers with number symbols. While on the indicator of recognizing vowel and consonant symbols, there is no difference in ability between male and female students.